Correlation of Serum Sodium Level with Severity of Hepatic Encephalopathy - Shah Zeb, Muhammad Abbas, Kamran Ahmad Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine correlation of serum sodium levels with severity of hepatic encephalopathy (HE). Study Design: A Cross-sectional study. Place and Duration of the Study: Department of Medicine, Mardan Medical Complex, Mardan from 1st October 2020 to 30th April 2021. Methodology: A total of 170 patients of both genders with liver cirrhosis presenting with HE aged 35-65 years were included. Under aseptic conditions, blood was taken dispatched to institutional laboratory for serum sodium levels. Severity of hyponatremia was compared with study variables along with grades of HE. Post stratification chi square test was applied and p<0.05 was considered statistically significant. Results: Out of a total of 170 patients, 140 (82.4%) we male. Overall, mean age was 55.0±3.87 years while 130 (76.5%) patients were aged between 51 to 65 years. Grading of HE revealed most of the patients, 73 (42.9%) to be having grade-III. Grading of hyponatremia revealed that 101(59.4%) patients had mild hyponatremia, 50 (29.4%) moderate hyponatremia while 19 (11.2%) had profound hyponatremia. Age distribution was found to have significant association with severity of hyponatremia (p<0.0001). Significant correlation between grades of HE and severity of hyponatremia was noted as 15 (78.9%) out of 19 profound hyponatremia cases belonged to HE grade-III whereas all 50 patients of moderate hyponatremia belong to HE grade III and IV (p<0.0001). Conclusion: Hyponatremia was observed to be a very common abnormality among patients of liver cirrhosis presenting with hepatic encephalopathy. Significant correlation of hyponatremia was found with respect to HE grades as severity of hyponatremia increased with severity of HE grades. Higher age groups had significant association with higher degree of hyponatremia. Keywords: Hepatic encephalopathy, hyponatremia, liver cirrhosis, serum sodium.